Version control with Subversion - Collins-Sussman, Ben (O'Reilly Media, 2004)
One of the greatest frustrations in most software projects is version control: the art of managing changes to information. Today's increasingly fast pace of software development--as programmers make small changes to software one day only to undo them the next--has only heightened the problem; consecutive work on code or single-programmer software is a rare sight these days. Without careful attention to version control, concurrent and collaborative work can create more headaches than it solves. This is where Subversion comes into play. Written by members of the Subversion open source developm.